Growth and Development Indicators of Kids Under Experiment - T.Q. Naurizov; F.U Kaniyazova (International Journal on Integrated Education, 2021)
In the " Strategy actions in five priority areas of the Republic of Uzbekistan in 2017-2021 years", approved by the Decree of the President of the Republic of Uzbekistan No. PQ-4947 dated February 7, 2017, aimed at accelerating the development of animal husbandry in the coming years, according to the Resolution on measures for modernization and rapid development of agriculture, the main focus is on a number of tasks. It is known that animal husbandry is one of the leading fields of agriculture and plays an important role in providing the population with food. Along with livestock, it provides an increase in the number of goats, an increase in their breeding and productivity qualities, as well as an increase in production from year to year.